Petrogenic Hydrocarbons in the Peace-Athabasca Delta and their Potential for Microbial Degradation - Roy, Michelle-Claire (Université d'Ottawa / University of Ottawa, 2019)
Microbial biodegradation is the primary mechanism by which petrogenic hydrocarbons (PHCs) are removed from the environment. Though hydrocarbon biodegradation is widely studied in marine systems, knowledge of how it occurs in freshwater systems is still lacking. The Peace-Athabasca Delta (PAD), located in northeastern Alberta, is an ideal location to study microbial hydrocarbon degradation since it has a long history of exposure to PHCs. What’s more, these PHCs are predominately sourced from bituminous deposits and are therefore relevant to the Canadian Oil Sands Industry. This thesis investigated the genetic potential for hydrocarbon degradation of PHCs via metagenomic reconstruction of microbial communities in lakes of the Peace and Athabasca Deltas, as well as reference lakes in the nearby boreal uplands. In order to properly evaluate the microbial community and its potential for hydrocarbon degradation, a comprehensive analysis of PHCs (including n-alkanes, polycyclic aromatic compounds (PACs), and petroleum biomarkers of terpanes, hopanes, and steranes) was performed. PHC analysis showed that n-alkanes in lake sediments from all three regions were highly similar and predominately biogenic, while PAC composition was significantly different in each region. Restricted-drainage lakes of the Athabasca Delta had the highest concentrations of PACs from petrogenic sources. Closed-drainage lakes in the Peace Delta had lower concentrations of PACs that likely originated from a mixture of pyrogenic and petrogenic sources. Closed-drainage lakes in the boreal upland region had the lowest concentrations of PACs likely sourced from pyrogenic wood combustion with traces of petrogenic PACs, possibly from atmospheric deposition of dust. Petroleum biomarkers of terpanes, hopanes, and steranes were successfully used to identify the long-range fluvial, and possibly atmospheric, transport of bituminous compounds more than one hundred kilometers from their potential source. This validates the future use of these biomarkers in environmental forensics. Microbial communities in all three regions under study were highly diverse, and their composition was significantly different in both sediment and water. Targeted gene analysis identified a total of 3885 genes involved in the degradation of n-alkanes and PACs in sediment and water. The results show that organic carbon, nitrogen, and sulfur content, as well as PAC and short-chain alkane concentrations were important chemical predictors of change in degradation gene composition. Furthermore, genes for anaerobic degradation of PHCs were identified in syntrophic bacteria, methanogens, nitrate and sulfate reducers, demonstrating the potential for syntrophic hydrocarbon degradation in PAD lakes. Though this thesis confirms the genetic potential for hydrocarbon degradation in PAD and boreal upland lakes, further research is necessary to determine whether these microbial communities can actively degrade the PHCs present in these lakes.
Keywords: Metagenomics; Polycyclic Aromatic Compounds; Biodegradation; Petroleum Biomarkers; Peace-Athabasca Delta; Oil Sands; Bitumen